Research progress on role of programmed cell death in silicosis and its possible mechanisms - Jing WU; Xue YI; Jie WANG (环境与职业医学, 2023)
Silicosis is a common occupational disease caused by long-term inhalation of large amounts of free SiO2 dust and deposition in lung tissues, characterized by the formation of silicon nodules and diffuse fibrosis of lung tissues. Silicosis is one of the most common and serious occupational diseases in China, and its treatment imposes a huge economic burden on individuals and the country. The formation mechanism of silicosis is very complex, and no early screening indicators, effective drugs, and treatment methods are available yet. The current diagnosis of silicosis is based on occupational history and chest radiography findings, and it is irreversible once pulmonary fibrosis develops. Moreover, as silicosis is a continuously progressive disease, even if silicosis patients stop exposure to free SiO2 dust, their pulmonary fibrosis will continue to develop and deteriorate. Programmed cell death (autophagy, apoptosis, ferroptosis, etc.) is a key factor involved in the development of silicosis. This article summarized the important roles of programmed cell death, including autophagy, apoptosis, and ferroptosis, in silicotic fibrosis, and concluded that regulating different programmed cell death and related signaling pathways through effective means may delay the process of silicosis fibrosis, providing new ideas and clues for exploring potential mechanisms of silicosis formation and formulating prevention and treatment strategies.